Prescription Opioids and Risk of Dementia or Cognitive Decline: A Prospective Cohort Study. Issue 8 (20th August 2015) - Dublin, Sascha; Walker, Rod L.; Gray, Shelly L.; Hubbard, Rebecca A.; Anderson, Melissa L.; Yu, Onchee; Crane, Paul K.; Larson, Eric B.
Abstract : Objectives: To determine whether prescription opioid use is associated with higher dementia risk or greater cognitive decline. Design: Prospective cohort study. Setting: Group Health, an integrated healthcare delivery system. Participants: Community‐dwelling individuals aged 65 and older without dementia with at least 10 years of Group Health enrollment at baseline (N = 3, 434; median age 74). Measurements: The Cognitive Abilities Screening Instrument (CASI) was administered every 2 years. Low scores triggered detailed evaluation, and a multidisciplinary committee assigned dementia diagnoses. From computerized pharmacy data, cumulative opioid exposure was defined as total standardized doses (TSDs) dispensed over 10 years (excluding the most recent year because of possible prodromal symptoms). For comparison, use of nonsteroidal anti‐inflammatory drugs (NSAIDs), characterized similarly, was examined. Dementia risk was analyzed using Cox proportional hazards models and CASI trajectory using linear regression models and generalized estimating equations. Results: Seven hundred ninety‐seven participants (23%) developed dementia over a mean follow‐up of 7.3 years; 637 (19%) had possible or probable Alzheimer's disease. For cumulative opioid use, the hazard ratios (HRs) for dementia were 1.06 (95% confidence interval (CI) = 0.88–1.26) for 11 to 30 TSDs, 0.88 (95% CI = 0.70–1.09) for 31 to 90 TSDs, and 1.29 (95% CI = 1.02–1.62) for 91 or more TSDs, versus 0 to 10 TSDs. A similar pattern was seen for NSAID use. Heavier opioid use was not associated with more‐rapid cognitive decline. Conclusion: People with the heaviest opioid or NSAID use had slightly higher dementia risk than people with little or no use. These results may reflect an effect of chronic pain on cognition or residual confounding. Although opioids have other risks, little evidence of long‐term cognitive harm specific to opioids was found.